TGT vs STAD: Comparing vocational students’ performance between two cooperative learning models - Pratiwi, Aulia Cahya; Khasanah, Uswatun (Universitas Ahmad Dahlan, 2025)
Various factors – such as low interest, motivation, and poor problem-solving skills – contribute to vocational high school students' low mathematics learning outcomes. The cooperative learning models of Teams Games Tournament (TGT) and Student Team Achievement Division (STAD) are the alternative teaching strategies proven to improve student learning outcomes. This study aims to compare the effects of the two models on the mathematics learning outcomes of eleventh-grade students at SMK Negeri 1 Salam – a vocational high school in Indonesia. The research uses a quantitative approach with a true experimental design of the posttest-only control group design type. We randomly selected two classes from a homogeneous population, which applied the TGT model to one class and the STAD model to the other. They used a learning outcome test that experts had validated and tested for reliability. Data were analyzed using the independent sample t-test and one-tailed test. The research results show a significant difference in the influence between the TGT and STAD models on mathematics learning outcomes, with the average score of the TGT group being higher (78.57) compared to the STAD group (74.11). One-tailed tests show that the TGT model has a significantly greater impact than STAD. Thus, the TGT model is considered more effective in improving the mathematics learning outcomes of vocational school students because it can create a competitive, enjoyable learning atmosphere and encourage active student participation.